Religious radicalism after the Arab uprisings - Alterman, Jon B. (CSIS report., 2015)
The Arab uprisings of 2011 created unexpected opportunities for religious radicals. Although many inside and outside the region initially saw the uprisings as liberal triumphs, illiberal forces have benefitted disproportionately. In Tunisia, formally marginalized jihadi-salafi groups appealed for mainstream support, and in Egypt, the Muslim Brotherhood triumphed in elections. Even in Saudi Arabia, not known for either lively politics or for political entrepreneurship, a surprising array of forces praised the rise of 'Islamic democracy' under a Muslim Brotherhood banner. Yet, at the same time, the Arab Spring reinforced regional governments' advantages. The chaos engulfing parts of the region has convinced some citizens that they were better off with the governments they had, and many governments successfully employed old and new tools of repression to reinforce the status quo. In the Middle East, conflicts that many thought were coming to an end will continue, as will the dynamism and innovation that have emerged among radical and opposition groups. To face the current threats, governments will need to use many of their existing tools skillfully, but they will also need to judge what tools will no longer work, and what new tools they have at their disposal. The stakes could not be higher.